Evidence of vacuolar-ATPase gene mediated RNA interference on Systena frontalis (F) (Coleoptera: Chrysomelidae) adults - Govindaraju, Ramkumar; Vavilapalli, Rajesh; Joseph, Shimat V. (Frontiers in agronomy, 2025)
Systena frontalis (F) (Coleoptera: Chrysomelidae) is a serious polyphagous pest in containerized ornamental nurseries in the central, mid-west, and eastern United States. Adults feed on plant foliage, causing shothole damage, and the affected plants are rarely salable. We studied the exogenous application of double-standard RNA (dsRNA) on the adult S. frontalis by targeting three vATPase subunit genes (A, D, and E). To evaluate RNAi efficacy, we measured adult feeding damage, survival, and gene expression levels using quantitative RT-PCR (qRT-PCR). Six concentrations-10, 30, 40, 50, 60, and 70 µg/cm 2 of dsRNA were applied to panicled hydrangea leaves. The dsRNA was designed to inhibit the expression of three vATPase genes, A, D, and E subunits, and assessed how different amounts of cognate dsRNA affect the silencing of these genes. Adult S. frontalis feeding damage was significantly reduced with ds vATPase -A, -D, and -E at 3 d post-exposure. Up to 50% reduction in feeding damage was observed at 70 µg per cm 2 . The survival of adult S. frontalis was not reduced after ingestion of ds vATPase -A, -D, and -E treatment. When the pre-exposed adult S. frontalis to ds vATPase -A, -D, and -E was transferred to nontreated foliage for 1 d, a significant reduction in feeding damage was observed across different tested concentrations of ds vATPase -A, -D, and -E. A dose-response in the expression of dsRNA was observed in S. frontalis adults exposed to ds vATPase -A, -D, and -E treated foliage after 4 d. The results suggest that these three RNAi products can potentially manage S . frontalis in ornamental nurseries.